Quality of Work Life among Women Employees Working in RMG Sector of Bangladesh - Hossain, Tanjela; Shirazi, Hasan (Global Disclosure of Economics and Business, 2018)
“Quality of work life” has become the buzzword for the contemporary organization. Employees are more concern about their work environment ever, which is one of the most important factors to determine the quality of work life (QWL). It refers to the favorableness or unpleasantness of a job environment for people. The increased complexity of today’s work environment poses several challenges, especially for women employees who are working in different garment factories. It is now the high time for the Ready-made Garment (RMG) sector to be aware of improving the QWL. Our study focused on the factors influencing the quality of work life of women employees, their level of job satisfaction. We have tried to assess the QWL of women employees working in selected garment factories which are located in Gazipur district. We have collected data through a semi-structured questionnaire from a sample of 500 women employees. The findings of the study project various indications about concerned issues where the organization can concentrate to bring about better QWL life so that they get more satisfied women workforce. For statistical analysis mean, percentage, hypothesis testing, ranking order method and weighted average method were calculated. The ultimate findings of the study reveal that there is a significant relationship between work experience and participation in decision making for women employees. The survey study also shows that authority’s willingness is also an influential parameter to improve the QWL. Another interesting finding of our survey focuses that women employees have been given the least priority to salary as a measure to enhance QWL.